MAINARDES, J.; STREMEL, S. (Eds.). Education Policy research: epistemological and theoretical issues. Curitiba: Brazil Publishing, 2020. 270 p. (Práxis Educativa, 2020)
Mainardes, J., & Stremel, S. (2020). Education Policy research: epistemological and theoretical issues. Curitiba: Brazil Publishing. 270 p.